The Effect of Profitability and Managerial Ownership as Corporate Governance Mechanisms on Company Value in the Industrial Sector Listed on the IDX in 2022-2024 - Das, Nidia Anggreni; Sukraini, Juita; Sari, Resmita; Afni, Susi; Maharani, Dovita; Risanti, Dezy; Sidiq, Yodika; Kholiq, Wildan (Research Collaboration Community (Rescollacom), 2025)
Indonesia's manufacturing sector is one of the largest contributors to national GDP, but also faces challenges in managing governance and operational efficiency. This study aims to analyze the effect of profitability and managerial ownership as corporate governance mechanisms on firm value. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022 to 2024. Profitability is measured using Return on Assets (ROA), while managerial ownership is measured based on the percentage of shares owned by managers or internal parties. The data used are secondary data obtained from the company's annual financial reports published on the official IDX website. Data collection was carried out using the documentation method, and the sample was determined using the purposive sampling method. Data analysis was performed using multiple linear regression to test the simultaneous and partial effects of the independent variables on the dependent variable. The results found that profitability (X1) has a regression coefficient of -1.946 with a significance value of 0.056 and managerial ownership as a corporate governance mechanism (X2) has a regression coefficient of 0.261 with a significance value of 0.170. Simultaneously, these two independent variables also do not have a significant effect in explaining changes in company value, with a model capability of only 12.4%.